Reducing the network bandwidth requirements for 360o immersive video streaming - Luca De Cicco; Saverio Mascolo; Vittorio Palmisano; Giuseppe Ribezzo (Internet Technology Letters, 2019)
Virtual Reality/Augmented Reality applications are getting increasingly popular and new services are emerging in a diverse set of fields such as entertainment, art, e-health, and smart factories. 360° videos are an advancement of classical two-dimensional videos giving the user the impression of being immersed at the center of a scene that can be explored freely and dynamically by simply turning the head to a given region of interest (RoI). Providing a high Quality of Experience to users when streaming 360° videos over the Internet is particularly challenging due to the very high bandwidth requirements. In this letter, a scaling technique to reduce bandwidth requirements to stream omni-directional videos is presented. An experimental investigation of the proposed approach has shown that it is possible to obtain a reduction of the required bitrate up to around 50% while gracefully degrading visual quality far from the RoI.
Keywords: augmented reality/virtual reality; experimental performance evaluation; immersive video streaming; MPEG-DASH